Insights revealed by the co‐crystal structure of the Saccharomyces cerevisiae histidine phosphotransfer protein Ypd1 and the receiver domain of its downstream response regulator Ssk1 - Branscum, Katie M. (Protein Sci, 2019)
Two‐component signaling systems are the primary means by which bacteria, archaea, and certain plants and fungi react to their environments. The model yeast, Saccharomyces cerevisiae, uses the Sln1 signaling pathway to respond to hyperosmotic stress. This pathway contains a hybrid histidine kinase (Sln1) that autophosphorylates and transfers a phosphoryl group to its own receiver domain (R1). The phosphoryl group is then transferred to a histidine phosphotransfer protein (Ypd1) that finally passes it to the receiver domain (R2) of a downstream response regulator (Ssk1). Under normal conditions, Ssk1 is constitutively and preferentially phosphorylated in the phosphorelay. Upon detecting hyperosmotic stress, Ssk1 rapidly dephosphorylates and activates the high‐osmolarity glycerol (HOG) pathway, initiating a response. Despite their distinct physiological roles, both Sln1 and Ssk1 bind to Ypd1 at a common docking site. Co‐crystal structures of response regulators in complex with their phosphorelay partners are scarce, leaving many mechanistic and structural details uncharacterized for systems like the Sln1 pathway. In this work, we present the co‐crystal structure of Ypd1 and a near wild‐type variant of the receiver domain of Ssk1 (Ssk1‐R2‐W638A) at a resolution of 2.80 Å. Our structural analyses of Ypd1‐receiver domain complexes, biochemical determination of binding affinities for Ssk1‐R2 variants, in silico free energy estimates, and sequence comparisons reveal distinctive electrostatic properties of the Ypd1/Ssk1‐R2‐W638A complex that may provide insight into the regulation of the Sln1 pathway as a function of dynamic osmolyte concentration.